Innovation of Shallot (Allium Ascalonicum L) Essential Oil for Fever Reduction in Infants Post DTaP Immunization - Setiawandari Setiawandari; Istiqomah Istiqomah; Marquita Da Silva Ximenes (Jurnal Ilmiah Kesehatan, 2021)
DTaP vaccination causes an increased body temperature or fever in most infants. There are pharmacological or non-pharmacological efforts to reduce fever in infants post-DTaP immunization. In addition, shallots are a family medicinal plant in Indonesia commonly used to reduce fever. There should be innovation in the dosage form of shallots so their use is more effective and efficient. This study analyzes the effect of shallot essential oil on fever reduction in infants post-DTaP vaccination. It was a quasi-experimental research design, with one group pre and post-test design. The population of this research was all infants aged 1-12 months who were enrolled in the infant cohort in 2020 at Independent Midwifery Practice (IMP) Istiqomah from May to August 2020. Meanwhile, there were 20 samples by accidental sampling. The research instruments were shallot extract oil, a digital thermometer, and an observation sheet. The data analysis used the Repeated Measures Anova test. The results showed that the mean body temperature before immunization was 36.57 degrees Celcius, while after the experiment was 36.9 degrees Celcius. The statistical test results value ρ = 0.000. There was a significant difference in the mean body temperature from time to time in infants with shallot essential oil administration. This study concludes that shallot essential oil reduces fever in infants post-DTaP immunization. Further research should use a control group, more significant samples, and inclusion criteria limitation.